Practices related to late‐onset sepsis in very low‐birth weight preterm infants - Maria Regina Bentlin; Ligia M.S.S. Rugolo; Ligia S.L. Ferrari (Brazilian Society of Pediatrics, 2015)
Objective: To understand the practices related to late‐onset sepsis (LOS) in the centers of the Brazilian Neonatal Research Network, and to propose strategies to reduce the incidence of LOS. Methods: This was a cross‐sectional descriptive multicenter study approved by the Ethics Committee. Three questionnaires regarding hand hygiene, vascular catheters, and diagnosis/treatment of LOS were sent to the coordinator of each center. The center with the lowest incidence of LOS was compared with the others. Results: All 16 centers answered the questionnaires. Regarding hand hygiene, 87% use chlorhexidine or 70% alcohol; alcohol gel is used in 100%; 80% use bedside dispensers (50% had one dispenser for every two beds); practical training occurs in 100% and theoretical training in 70% of the centers, and 37% train once a year. Catheters: 94% have a protocol, and 75% have a line insertion team. Diagnosis/treatment: complete blood count and blood culture are used in 100%, PCR in 87%, hematological scores in 75%; oxacillin and aminoglycosides is the empirical therapy in 50% of centers. Characteristics of the center with lowest incidence of LOS: stricter hand hygiene; catheter insertion and maintenance groups; use of blood culture, PCR, and hematological score for diagnosis; empirical therapy with oxacillin and aminoglycoside. Conclusion: The knowledge of the practices of each center allowed for the identification of aspects to be improved as a strategy to reduce LOS, including: alcohol gel use, hand hygiene training, implementation of catheter teams, and wise use of antibiotic therapy.